A sociopsychological analysis of agroforestry adoption in Flanders: understanding the discrepancy between conceptual opportunities and actual implementation. Issue 9 (20th October 2016) - Borremans, Lieve; Reubens, Bert; Van Gils, Bert; Baeyens, Dorien; Vandevelde, Céline; Wauters, Erwin
ABSTRACT: While the opportunities of modern agroforestry systems are increasingly recognized by policymakers, consultants, researchers, and educators, the response of farmers to the recent subsidy program for alley cropping systems in Flanders is relatively low. Therefore, in this study, a mixed method technique, including a survey ( n = 86), interviews ( n = 33), and a GIS analysis, is used to better understand the reasons behind this implementation gap. The study showed that 55% of the Flemish farmers are not familiar with agroforestry and that the intention to engage in agroforestry is very low. As a result, alley cropping in Flanders remains sparse with only around 30 farmers known to be consciously engaged in the practice. In the last couple of years, these pioneers have installed one or more agroforestry plots (average surface area of 2.3 ha) that often combine a variety of trees with grassland. Whereas negative perceptions of Flemish farmers are mainly related to compatibility and profitability of such a farming system, pioneers consider legal issues, such as land tenure, the most pertaining drawback. Therefore, future research and policy and extension efforts should target these aspects in order to enhance further diffusion.